Can You Match These Friends? A Test of Genetic Similarity Theory. - Sandager, Katrina M.; Maves, Stephanie R. A.; Hubert, Sarah L. (My University, 2009)
Genetic similarity theory proposes that in selecting social partners, people choose individuals who resemble themselves at the genetic level. In a novel test of this theory, we asked outside raters to view photographs and match pairs of same-sex friends on the basis of their physical appearance.
Color poster with text, images, and graphs describing research conducted by Katrina M. Sandager, Stephanie R. A. Maves, and Sarah L. Hubert, advised by April Bleske-Rechek.
Keywords: Friendship--Physiological aspects; Friendship--Sex differences; Friendship--Social aspects; Posters